Heat-conducting color-adjustable photothermal conversion film and preparation method thereof

By using the design of multi-layer composite structures in the photo-heat conversion film and precise control of the deposition parameters, the preparation complexity and stability of the photo-heat conversion film in the existing technology are solved, efficient thermal conductivity and color adjustment are achieved, and light is improved Thermal conversion efficiency and adaptability.

CN119121158APending Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411243505.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-12
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the preparation process, existing photothermal conversion films have problems such as complex process, strong equipment dependence, high raw material cost, low photothermal conversion efficiency and poor stability, making it difficult to achieve efficient thermal conductivity and color customization at the same time.

Method used

Using a thermally conductive color tunable light-thermal conversion film composed of a reflective layer, an absorbing layer and an anti-reflective layer, a multi-layer composite structure of Ag deposition layer, Ag, Cu co-doped MoS2 layer and SiO2 deposition layer is combined with precise control of the deposition parameters. With the argon flow rate and RF power supply power, it forms an efficient and stable film.

Benefits of technology

It achieves stable thermal conductivity and color performance under different environments, improves photothermal conversion efficiency and adaptability, and has higher visual design advantages and wide applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005029951250000011
    Figure HDA0005029951250000011
  • Figure HDA0005029951250000012
    Figure HDA0005029951250000012
  • Figure HDA0005029951250000013
    Figure HDA0005029951250000013
Patent Text Reader

Abstract

The invention discloses a heat-conducting color-adjustable photothermal conversion film and a preparation method thereof, and belongs to the technical field of solar heat collectors. According to the heat-conducting color-adjustable photo-thermal conversion film disclosed by the invention, due to the adoption of a novel material combination of the reflecting layer, the absorbing layer and the antireflection layer, the film keeps efficient heat-conducting property, and meanwhile, the color is flexibly adjusted. Compared with the prior art, the heat conduction color adjustable photothermal conversion film can keep stable heat conduction efficiency and color expression in different environments. The method has the advantages of higher photo-thermal conversion efficiency, wider adaptability and more personalized visual design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar collectors, and in particular relates to a thermally conductive, color-adjustable light-to-heat conversion film and a preparation method thereof. Background Art

[0002] Global warming caused by carbon dioxide has become a serious problem facing society. The effective use of renewable clean energy, especially solar energy, is considered to be a promising solution to global warming. At present, solar thermal conversion is widely used in people's daily life, such as solar collectors. Collectors mainly use absorbing films coated on the surface to achieve photothermal conversion. Photothermal conversion films have strong thermal conductivity and high absorption capacity in the visible-near infrared wavelength range of the solar radiation spectrum.

[0003] Solar spectrum selective absorption films are divided into (a) intrinsic absorption type (semiconductor and transition metal), (b) semiconductor metal tandem type, (c) multilayer interference type (TiOxNy), (d) metal ceramic composite type (M-AlN), (e) surface texture type (optical trap) Although there are many types of films, the most widely used are multilayer interference type and metal ceramic composite photothermal conversion films. Common preparation methods: coating method, electroplating method, anodizing, vacuum coating method, chemical vapor deposition (CVD) and magnetron sputtering (PVD), etc. The current preparation technology of photothermal conversion films has the following main disadvantages: 1) Complex preparation process: The preparation of traditional photothermal conversion films usually involves multiple steps and delicate operations, which not only increases production costs, but also may lead to accumulated errors in the production process, affecting the performance of the final product; 2) Strong equipment dependence: The preparation of high-performance photothermal conversion films requires specific equipment and facilities. These equipment are often expensive and require regular maintenance and calibration, which increases the technical threshold and cost; 3) High raw material costs: Some high-performance photothermal conversion films require rare or expensive raw materials, which increases the preparation cost and limits their wide application; Low photothermal conversion efficiency: The photothermal conversion efficiency of existing photothermal conversion films is still limited, making it difficult to fully utilize solar energy; Poor stability: Some photothermal conversion films may experience performance degradation or damage after long-term use, which affects their service life and reliability. Summary of the invention

[0004] The purpose of the present invention is to provide a thermally conductive color-adjustable light-to-heat conversion film and a preparation method thereof, so as to solve the technical problem that existing films are difficult to achieve both thermal conductivity efficiency and color customization at the same time.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention discloses a thermally conductive color-adjustable light-to-heat conversion film, which comprises a reflective layer, an absorption layer and an anti-reflective layer arranged from top to bottom; wherein the reflective layer is an Ag deposition layer; the absorption layer is Ag and Cu co-doped MoS 2 layer; the anti-reflection layer is SiO 2 Sedimentary layer.

[0007] The present invention also discloses a method for preparing the thermally conductive color-adjustable light-to-heat conversion film, comprising the following steps:

[0008] First, the gas pressure in the deposition chamber is adjusted, and in an inert gas environment, an Ag target is sputtered on the surface of the substrate to form an Ag deposition layer;

[0009] Then, the working gas pressure was adjusted, and Ag target, Cu target and MoS were sputtered simultaneously on the surface of the Ag deposition layer in an inert gas environment. 2 target, forming Ag, Cu co-doped MoS 2 layer;

[0010] In an inert gas environment, a molybdenum disulfide target was sputtered using a radio frequency power supply. 2 SiO 2 Sedimentary layer.

[0011] Furthermore, before the Ag target is sputtered, the substrate is ultrasonically cleaned with an ethanol solution for 20 to 25 minutes; and the surface roughness of the substrate is less than 30 nm.

[0012] Furthermore, when forming the Ag deposition layer, the pressure in the deposition chamber is adjusted to 10 -4 Pa~2×10 -4 Pa, and then when the Ag target is sputtered on the surface of the substrate, the working gas pressure in the deposition chamber is adjusted to 0.8Pa~1.0Pa, the inert gas environment is argon, and the gas flow rate of argon is 100sccm~120sccm.

[0013] Furthermore, when sputtering the Ag target, the radio frequency power used is 3W to 4W, and the sputtering time of the Ag target is 10min to 13min.

[0014] Further, Ag and Cu co-doped MoS 2 When forming a layer, the working gas pressure is adjusted to 0.8Pa~1.0Pa, the inert gas environment is argon, and the gas flow rate of argon is 107sccm~110sccm.

[0015] Further, Ag and Cu co-doped MoS 2When sputtering Ag target, the RF power used is 18W~22W; when sputtering Cu target, the RF power used is 12W~14.6W; when sputtering MoS 2 When the target is detected, the RF power used is 200W~220W.

[0016] Further, Ag and Cu co-doped MoS 2 When sputtering Ag target, Cu target and MoS 2 The target time is 90 minutes to 120 minutes.

[0017] Further, the formation of SiO 2 When depositing the layer, 100 sccm to 120 sccm of argon gas is introduced into the deposition chamber to form an inert gas environment, and the working gas pressure is adjusted to 0.8 Pa to 1.0 Pa.

[0018] Further, the formation of SiO 2 When depositing the layer, the radio frequency power used for sputtering the molybdenum disulfide target is 12W to 15W; the time for sputtering the molybdenum disulfide target is 9min to 12min.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention discloses a thermally conductive color-adjustable light-to-heat conversion film. Due to the use of a new material combination of a reflective layer, an absorption layer, and an anti-reflective layer, the film can achieve flexible color adjustment while maintaining high thermal conductivity. Compared with the prior art, the thermally conductive color-adjustable light-to-heat conversion film of the present invention can maintain stable thermal conductivity and color performance under different environments. It has higher light-to-heat conversion efficiency, wider adaptability, and more personalized visual design advantages.

[0021] The preparation method of the thermally conductive color-adjustable light-to-heat conversion film disclosed in the present invention comprises the following steps: depositing an Ag deposition layer, co-doping MoS with Ag and Cu, 2 Layer deposition and SiO 2 The preparation of the deposited layer achieves precise control of the film performance by setting the deposition parameters; first, the substrate is strictly surface treated and ultrasonically cleaned to ensure the adhesion and uniformity of the coating. Subsequently, in a vacuum environment, by precisely controlling the argon gas flow rate and key variables of the power supply parameters, the reflective layer, the absorption layer and the anti-reflection layer are deposited in sequence to form a multi-layer composite structure; this method not only ensures the purity and uniformity of the coating, but also optimizes the optical properties of the film through the design of the multi-layer composite structure. In addition, this method also has the advantages of high-precision control, high purity, high performance and wide applicability, providing an effective technical means for the preparation of efficient and stable thermally conductive color-adjustable photothermal conversion films. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the thermally conductive color-tunable light-to-heat conversion film prepared in Example 1;

[0023] Among them: Ag: 18W, Cu: 12W;

[0024] Figure 2 This is the EDS element surface distribution diagram of the thermally conductive color-tunable light-to-heat conversion film prepared in Example 1;

[0025] Among them: a-Scanning electron micrograph of Ag-Cu-MoS2; b-Surface element distribution of Ag-Cu-MoS2 film;

[0026] Figure 3 This is the XPS graph of the thermally conductive color-tunable light-to-heat conversion film prepared in Example 1;

[0027] Figure 4 This is a thermal imaging image of the thermally conductive color-tunable light-to-heat conversion film prepared in Example 1;

[0028] Among them: a-Ag-Cu-MoS 2 The actual temperature change of the film sample surface; b-thermal imaging picture of the highest temperature;

[0029] Figure 5 This is a real color picture of the thermally conductive color-adjustable light-to-heat conversion film prepared in Example 1. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0032] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0033] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0034] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0035] The present invention provides a thermally conductive color-adjustable light-to-heat conversion film, comprising a reflective layer, an absorption layer, and an anti-reflective layer arranged in sequence from bottom to top on a substrate; wherein the infrared reflective layer is an Ag deposition layer, and Ag and Cu co-doped MoS 2 It is the absorption layer and silicon dioxide is the anti-reflection layer.

[0036] The present invention also provides a method for preparing the above-mentioned thermally conductive color-adjustable light-to-heat conversion film, comprising the following steps:

[0037] Step 1: Surface preparation of the substrate.

[0038] Step 2: Place the substrate in an ethanol solution for ultrasonic cleaning.

[0039] Step 3: Deposition of reflective layer: Place in a vacuum chamber for evacuation, introduce argon, turn on bias for bias cleaning, first plate Ag as a metal reflective layer, adjust the working gas pressure and argon flow rate; turn on the Ag target DC power supply and adjust the current and voltage, turn on the sample stage speed control button, and adjust the rotation speed; finally, open the baffle and record the deposition time, and the preparation of the reflective layer is completed.

[0040] Step 4: Close the baffle first, adjust the working gas pressure, Ar gas flow, MoS 2 The target RF power supply adjusts the power; the Ag target DC power supply A adjusts the current and voltage to make its power different values, and the Cu target DC power supply B adjusts the current and voltage to make its power different values; after the adjustment is completed, the baffle is opened and the deposition time is recorded, and the absorption layer is prepared.

[0041] Step 5: introduce argon gas into the vacuum chamber and use a radio frequency power supply to sputter the molybdenum disulfide target; deposit a silicon dioxide layer on the absorption layer in step 4; and complete the preparation of the anti-reflection layer.

[0042] Preferably, in step 1, the surface roughness of the substrate is less than 30 nm.

[0043] Preferably, the ultrasonic cleaning time in step 2 is 20 to 25 minutes.

[0044] Preferably, in step 3, when depositing the reflective layer, the cleaned substrate material is placed in a vacuum and first evacuated to 10 -4 Pa~2×10 -4 Pa, turn on the bias voltage for bias cleaning. Ag is plated as a metal reflective layer, the working pressure is adjusted to 0.8Pa~1.0Pa, and the argon gas flow rate is 100sccm~120sccm. Turn on the Ag target DC power supply and adjust the current and voltage to 3W~4W, turn on the sample stage speed control button, adjust the speed to 12~15r / min, and finally open the baffle and record the deposition time as 10min~13min. The reflective layer is prepared.

[0045] Preferably, when depositing the absorption layer in step 4, first close the baffle, directly adjust the working gas pressure to 0.8Pa-1.0Pa, the argon gas flow rate to 107sccm-110sccm, and the MoS2 target RF power supply to 200W-220W. The Ag target DC power supply A adjusts the current and voltage to 18W-22W, and the Cu target DC power supply B adjusts the current and voltage to 12W-14.6W. After the adjustment is completed, open the baffle, and record the deposition time as 90min-120min, and the absorption layer is prepared.

[0046] Preferably, when depositing the anti-reflection layer in step 5, 100 sccm to 120 sccm argon gas is introduced into the vacuum chamber, and the working gas pressure is 0.8 Pa to 1.0 Pa; the RF power supply on the molybdenum disulfide target is turned on, and the current and voltage are adjusted to make the power 12 W to 15 W. After the adjustment is completed, the baffle is opened, and the deposition time is recorded as 9 min to 12 min. The preparation of the anti-reflection layer is completed.

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0049] Example 1

[0050] A method for preparing a thermally conductive color-adjustable light-to-heat conversion film comprises the following steps:

[0051] Step 1: Place the 1235 aluminum alloy with a surface roughness of less than 30 nm in an ethanol solution for ultrasonic cleaning for 15 min, place it in a deposition chamber, and evacuate it to 1x10 -4 Pa, turn on the bias voltage through Ar for bias cleaning, then adjust the working gas pressure in the deposition chamber to 0.8Pa, the argon gas flow rate to 100sccm, turn on the Ag target DC power supply and adjust the current and voltage to 3W, turn on the sample stage speed control button, adjust the speed to 12r / min, finally open the baffle and record the deposition time as 10min, and the preparation of the reflective layer (Ag deposition layer) is completed;

[0052] Step 2: Close the baffle first, directly adjust the working pressure to 0.8Pa, the argon gas flow rate to 107sccm, and the MoS 2 The target RF power supply is adjusted to 200W, the Ag target DC power supply A is adjusted to 20W, and the Cu target DC power supply B is adjusted to 13.3W. After the adjustment is completed, the baffle is opened and the deposition time is recorded as 90min. The absorption layer is prepared;

[0053] Step 3: Introduce 100 sccm of argon gas into the vacuum chamber, and the working gas pressure is 0.8 Pa; turn on the RF power supply on the molybdenum disulfide target, adjust the current and voltage to make its power 13.3 W, open the baffle after the adjustment, and record the deposition time as 9 minutes, and the anti-reflection layer is prepared.

[0054] Figure 1 This is the SEM image of the thermally conductive color-adjustable light-to-heat conversion film prepared in Example 1. It can be seen that the particle distribution is becoming more and more dense and the growth is uneven. Some large particles grow on small particles. The particle agglomeration is getting bigger and bigger. The size of each particle agglomeration is about 100nm. The distribution is more compact and disorderly, and basically no agglomeration gaps are observed. From the above, it can be concluded that moderate Ag and Cu doping promotes the growth of grains.

[0055] Figure 2 This is the EDS element distribution diagram of the thermally conductive color-adjustable light-to-heat conversion film prepared in Example 1. It can be seen that the pink Mo particles and the red S particles are evenly distributed in the figure. The pink material is not in a plane and belongs to a two-dimensional structure, indicating that the pink material belongs to MoS 2The blue particles are composed of Ag elements. It is observed that the Ag particles do not overlap significantly with the growth profile of the film surface, so the Ag particles are basically in the middle of the agglomerated particles. The green particles are Cu elements. It is observed that the Ag particles overlap significantly with the growth profile of the film surface and are evenly distributed on the particles, but the color is not obvious. Ag particles and Cu particles are dispersed in the MoS 2 In the medium. It can also be observed that the orange particles are O elements, which are very low in content compared to other elements, indicating that Cu and Ag are partially oxidized. In addition, the mapping images of each element are basically consistent in shape and evenly distributed. The content of related elements from high to low shows that the proportions of Ag, S, Cu, Mo and O are 29.67%, 22.30%, 18.82%, 15.47% and 13.74% respectively.

[0056] Figure 3 The XPS graph of the thermally conductive color-adjustable light-to-heat conversion film prepared in Example 1 shows that the binding energies of S, Mo, C, Ag, O, and Cu are 160.08, 233.08, 283.08, 367.08, 529.08, and 931.08 eV, respectively, indicating that Ag and Cu co-doped MoS 2 Therefore, the presence of these peaks in the high-resolution XPS spectrum indicates that Ag and Cu are successfully incorporated into MoS 2 middle.

[0057] Figure 4 The thermal imaging images of the thermally conductive color-tunable light-to-heat conversion film prepared in Example 1 show that the Ag-Cu-MoS 2 Under standard sunlight, the temperature of the film can rise from the ambient temperature of 15°C to above 90°C within 2 minutes, and it has good light-to-heat conversion performance. At the same time, it can quickly heat up and cool down in a short period of time. The heating state is stable after more than five consecutive cycles, and the film is in good condition.

[0058] Figure 5 The actual color map of the thermally conductive color-adjustable photothermal conversion film prepared. When the Ag doping concentration is 10.5% and the Cu doping concentration is 4.8%, the fabric presents a dark gray tone with a deep and uniform color. The colorimeter measures the reflectivity to be only 14.7%, showing strong absorption of light. When the Ag doping concentration is adjusted to 7.2% and the Cu doping concentration is 7.5%, the fabric becomes light gray, the reflectivity increases to 28.3%, and the light absorption is relatively weakened. These data not only reveal the close relationship between the film color and the doping concentration, but also reflect our in-depth research and fine control in the field of photothermal conversion technology, laying a solid foundation for future practical applications.

[0059] Example 2

[0060] A method for preparing a thermally conductive color-adjustable light-to-heat conversion film comprises the following steps:

[0061] Step 1: Place the 1235 aluminum alloy with a surface roughness of less than 30 nm in an ethanol solution for ultrasonic cleaning for 5 min, place it in a deposition chamber, and first evacuate it to 1x10 -4 Pa, turn on the bias voltage through Ar for bias cleaning, then adjust the working gas pressure in the deposition chamber to 0.8Pa, the argon gas flow rate to 100sccm, turn on the Ag target DC power supply and adjust the current and voltage to 3.5W, turn on the sample stage speed control button, adjust the speed to 12r / min, finally open the baffle and record the deposition time as 10min, and the preparation of the reflective layer (Ag deposition layer) is completed;

[0062] Step 2: First close the baffle, directly adjust the working gas pressure to 0.8Pa, the argon gas flow rate to 105sccm, the MoS2 target RF power supply to 180W, the Ag target DC power supply A and adjust the current and voltage to make its power 18W, the Cu target DC power supply B and adjust the current and voltage to make its power 12W, open the baffle after the adjustment is completed, and record the deposition time as 85min, and the absorption layer is prepared;

[0063] Step 3: Introduce 100 sccm of argon gas into the vacuum chamber, and the working gas pressure is 0.8 Pa; turn on the RF power supply on the molybdenum disulfide target, adjust the current and voltage to make its power 12 W, open the baffle after the adjustment, and record the deposition time as 8 minutes, and the anti-reflection layer is prepared.

[0064] Example 3

[0065] A method for preparing a thermally conductive color-adjustable light-to-heat conversion film comprises the following steps:

[0066] Step 1: Place the 1235 aluminum alloy with a surface roughness of less than 30 nm in an ethanol solution for ultrasonic cleaning for 6 min, place it in a deposition chamber, and first evacuate it to 1x10 -4 Pa, turn on the bias voltage through Ar for bias cleaning, then adjust the working gas pressure in the deposition chamber to 0.8Pa, the argon gas flow rate to 100sccm, turn on the Ag target DC power supply and adjust the current and voltage to make its power 4W, turn on the sample stage speed control button, adjust the speed to 12r / min, finally open the baffle and record the deposition time as 10min, and the preparation of the reflective layer (Ag deposition layer) is completed;

[0067] Step 2: First close the baffle, directly adjust the working gas pressure to 0.8Pa, the argon gas flow rate to 108sccm, the MoS2 target RF power supply to 190W, the Ag target DC power supply A and adjust the current and voltage to make its power 15W, the Cu target DC power supply B and adjust the current and voltage to make its power 13W, open the baffle after the adjustment is completed, and record the deposition time as 95min, and the absorption layer is prepared;

[0068] Step 3: Introduce 100 sccm of argon gas into the vacuum chamber, and the working gas pressure is 0.8 Pa; turn on the RF power supply on the molybdenum disulfide target, adjust the current and voltage to make its power 14 W, open the baffle after the adjustment, and record the deposition time as 10 minutes, and the anti-reflection layer is prepared.

[0069] Example 4

[0070] A method for preparing a thermally conductive color-adjustable light-to-heat conversion film comprises the following steps:

[0071] Step 1: Place a 1235 aluminum alloy with a surface roughness of <30 nm in an ethanol solution for ultrasonic cleaning for 4 minutes, place it in a deposition chamber, first evacuate it to 1x10^-4Pa, pass Ar to turn on the bias for bias cleaning, then adjust the working pressure in the deposition chamber to 0.8Pa, the argon gas flow rate to 100sccm, turn on the Ag target DC power supply and adjust the current and voltage to 2.5W, turn on the sample stage speed control button, adjust the speed to 12r / min, finally open the baffle and record the deposition time as 10min, and the preparation of the reflective layer (Ag deposition layer) is completed;

[0072] Step 2: First close the baffle, directly adjust the working gas pressure to 0.8Pa, the argon gas flow rate to 106sccm, the MoS2 target RF power supply to 210W, the Ag target DC power supply A and adjust the current and voltage to make its power 22W, the Cu target DC power supply B and adjust the current and voltage to make its power 14W, open the baffle after the adjustment is completed, and record the deposition time as 80min, and the absorption layer is prepared;

[0073] Step 3: Introduce 100 sccm of argon gas into the vacuum chamber, and the working gas pressure is 0.8 Pa; turn on the RF power supply on the molybdenum disulfide target, adjust the current and voltage to make its power 15 W, open the baffle after the adjustment, and record the deposition time as 7 minutes, and the anti-reflection layer is prepared.

[0074] Example 5

[0075] A method for preparing a thermally conductive color-adjustable light-to-heat conversion film comprises the following steps:

[0076] Step 1: Place the 1235 aluminum alloy with a surface roughness of <30 nm in an ethanol solution for ultrasonic cleaning for 5 minutes, place it in a deposition chamber, first evacuate to 1x10^-4Pa, pass Ar to turn on the bias for bias cleaning, then adjust the working pressure in the deposition chamber to 0.8Pa, the argon gas flow rate to 100sccm, turn on the Ag target DC power supply and adjust the current and voltage to 3W, turn on the sample stage speed control button, adjust the speed to 12r / min, finally open the baffle and record the deposition time as 10min, and the preparation of the reflective layer (Ag deposition layer) is completed;

[0077] Step 2: First close the baffle, directly adjust the working gas pressure to 0.8Pa, the argon gas flow rate to 107sccm, the MoS2 target RF power supply to 220W, the Ag target DC power supply A and adjust the current and voltage to 25W, the Cu target DC power supply B and adjust the current and voltage to 15W, open the baffle after the adjustment is completed, and record the deposition time as 90min, and the absorption layer is prepared;

[0078] Step 3: Introduce 100 sccm of argon gas into the vacuum chamber, and the working gas pressure is 0.8 Pa; turn on the RF power supply on the molybdenum disulfide target, adjust the current and voltage to make its power 16 W, open the baffle after the adjustment, and record the deposition time as 9 minutes, and the anti-reflection layer is prepared.

[0079] The thermally conductive color-adjustable light-to-heat conversion film obtained by the present invention is analyzed for its surface morphology. When the working pressure and substrate temperature are determined, Ag-Cu-MoS with different Ag / Cu ratios 2 In the thin film, all particles show a relatively uniform growth distribution. When the Ag / Cu ratio changes, the agglomeration size of the particles also changes. It can be concluded that moderate Ag and Cu doping promotes the growth of grains, thereby greatly increasing the absorption rate.

[0080] XRD and Raman analysis of the film phase structure revealed that the addition of Ag and Cu had a significant effect on the MoS 2 The crystal structure of AgNPs was not affected. In addition, since all diffraction peaks were narrow and sharp, it showed that the film had good crystallinity. The stable Raman characteristic peaks indicated that uniform MoS was successfully synthesized on AgNPs. 2 The peak shapes under different powers remain unchanged and the morphology is almost the same. 2 2. It has higher stability.

[0081] The film of the present invention has excellent optical properties and light-to-heat conversion performance. 2 After doping with Ag NPs and Cu NPs, Ag-Cu-MoS2 The absorption intensity is similar to that of single element MoS 2 Compared with the previous study, the absorption edge of Ag-Cu-MoS was significantly increased and shifted to the near-infrared region. The highest absorption rate was 94% when the Ag power was 20W and the Cu power was 13.3W. 2 Under standard sunlight, the film can rise from ambient temperature of 15°C to above 90°C within 2 minutes, and has good light-to-heat conversion performance. At the same time, it can quickly heat up and cool down in a short period of time. The temperature rise state is stable after more than five consecutive cycles, and the film is in good condition. This shows that the film has excellent light-to-heat conversion performance.

[0082] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A thermally conductive color-adjustable light-to-heat conversion film, characterized in that: The thermally conductive color-adjustable light-to-heat conversion film includes a reflective layer, an absorption layer and an anti-reflective layer from top to bottom; wherein the reflective layer is an Ag deposition layer; the absorption layer is an Ag and Cu co-doped MoS2 layer; and the anti-reflective layer is a SiO2 deposition layer.

2. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 1, characterized in that: The following steps are involved: First, the gas pressure in the deposition chamber is adjusted, and in an inert gas environment, an Ag target is sputtered on the surface of the substrate to form an Ag deposition layer; Then, the working gas pressure is adjusted, and in an inert gas environment, Ag target, Cu target and MoS2 target are sputtered simultaneously on the surface of the Ag deposition layer to form a MoS2 layer co-doped with Ag and Cu; In an inert gas environment, a molybdenum disulfide target is sputtered using a radio frequency power supply to form a SiO2 deposition layer on the Ag and Cu co-doped MoS2 layer.

3. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: The substrate is ultrasonically cleaned with an ethanol solution for 20 to 25 minutes before the Ag target is sputtered; the surface roughness of the substrate is less than 30 nm.

4. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the Ag deposition layer, first adjust the pressure in the deposition chamber to 10 -4 Pa~2×10 -4 Pa, and then when the Ag target is sputtered on the surface of the substrate, the working gas pressure in the deposition chamber is adjusted to 0.8Pa~1.0Pa, the inert gas environment is argon, and the gas flow rate of argon is 100sccm~120sccm.

5. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When sputtering the Ag target, the RF power used is 3W to 4W, and the sputtering time of the Ag target is 10min to 13min.

6. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the Ag and Cu co-doped MoS2 layer, the working gas pressure is adjusted to 0.8Pa~1.0Pa, the inert gas environment is argon, and the gas flow rate of argon is 107sccm~110sccm.

7. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the Ag and Cu co-doped MoS2 layer, the RF power used when sputtering the Ag target is 18W~22W; when sputtering the Cu target, the RF power used is 12W~14.6W; when sputtering the MoS2 target, the RF power used is 200W~220W.

8. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the Ag and Cu co-doped MoS2 layer, the sputtering time of the Ag target, the Cu target and the MoS2 target is 90 minutes to 120 minutes.

9. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the SiO2 deposition layer, 100 sccm to 120 sccm of argon gas is introduced into the deposition chamber to form an inert gas environment, and the working gas pressure is adjusted to 0.8 Pa to 1.0 Pa.

10. The method for preparing a thermally conductive color-adjustable light-to-heat conversion film according to claim 2, characterized in that: When forming the SiO2 deposition layer, the radio frequency power used for sputtering the molybdenum disulfide target is 12W to 15W; the time for sputtering the molybdenum disulfide target is 9 minutes to 12 minutes.

Citation Information

Patent Citations

  • Medium-and-low-temperature solar selective absorption thin film and preparation method thereof

    CN102620456A

  • Highly-doped MoOx-based photothermal conversion coating and preparation method thereof

    CN109972111A

  • Metal-doped molybdenum disulfide super-smooth film and preparation method thereof

    CN113088911A

  • Metal-doped molybdenum disulfide high-temperature-resistant composite film and preparation method thereof

    CN114959558A

  • Molybdenum sulfide-aluminum oxide solar energy absorbing coating and preparation method thereof

    CN117267962A